Pendampingan Penyusunan Rekomendasi Teknis Penanganan Banjir Berbasis Masyarakat Di Tingkat Desa/Kelurahan - Wulan Puspa Anggraini; Muhammad Latif; Mekarria Pangaribuan; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The increasing frequency and complexity of flood events at the village and urban neighborhood levels require mitigation approaches that extend beyond purely structural interventions and incorporate local capacity and community participation. This community engagement program aimed to develop and implement a community-based technical recommendation framework for flood mitigation through an empirical–participatory approach. The activities were conducted in several flood-prone urban villages in Sungai Serut District, Bengkulu City. Methods included participatory field surveys, flood-prone area mapping, focus group discussions, and qualitative evaluation of both processes and outcomes. The findings indicate that local drainage systems exhibit limited capacity due to inadequate dimensions, sedimentation, and insufficient routine maintenance, which are closely linked to land-use changes and community environmental practices. Active community involvement significantly enhanced the accuracy of problem identification, strengthened the social legitimacy of technical recommendations, and encouraged positive behavioral changes in environmental management. Furthermore, integrating the recommendations into local planning, budgeting, and monitoring mechanisms increased the likelihood of consistent implementation.